Relationship Between Coping Strategies and Anxiety Levels Among Hemodialysis Patients with Chronic Kidney Disease: A Cross-Sectional Study at Moewardi Hospital - Dennada Bagus Putra Perdana; Debree Septiawan; Lisetiawati Lisetiawati (Adi Husada Nursing Journal, 2025)
Anxiety is the most common psychopathological response among patients with chronic kidney disease (CKD). Coping strategies play a key role in helping individuals adapt to stressful conditions, yet no prior research has examined their relationship with anxiety levels among CKD patients undergoing hemodialysis at Moewardi Regional General Hospital, Surakarta. This observational cross-sectional study involved 37 CKD patients. Coping strategies were assessed using the Brief-COPE questionnaire, while anxiety levels were measured using the HADS-A instrument. Data were analyzed using Spearmanâ€™s rho correlation and the Mannâ€“Whitney test with a significance level of 0.05. Most participants were male (67.6%), elderly (29.7%), married (75.7%), and had undergone hemodialysis for â‰¥5 years (51.4%). The analysis revealed a very strong inverse correlation between coping strategies and anxiety levels (Ï = â€“0.793; p = 0.000). Significant differences were also found between patients using adaptive versus maladaptive coping strategies (p = 0.000). These findings indicate a significant association between coping strategies and anxiety severity in CKD patients receiving hemodialysis at Moewardi Regional General Hospital, Surakarta.